2013
DOI: 10.1111/ahe.12056
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Spermatogenesis in Zebu Bulls (bos taurus indicus)

Abstract: The objective of the research was to evaluate the efficiency of the spermatogenesis through the morphology of the testicular parenchyma in bulls of different zebu breeds. We used testicular fragments from bull of the breeds Nelore (n = 10), Polled Nelore (n = 6), Gyr (n = 5), Guzerat (n = 5) and Tabapuã (n = 5). The tissue was perfused with Karnovsky solution, included in glycol methacrylate and stained with toluidine blue-sodium borate 1%. Animals of the Nelore breed presented higher population of primary spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
6
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 26 publications
3
6
1
Order By: Relevance
“…In the present study, Sertoli cell and spermatogonia populations showed few variations between the animals evaluated. The average number of Sertoli cells observed was four per seminiferous tubule cross-section during stage 1 of CES and in the mean number of spermatogonia cells was two per cross-section, which were similar to the numbers observed as general averages by Andreussi et al [2] in the Nelore, Nelore mocho, Gir, Guzerá, and Tabapuã breeds, in addition to by Dias [35]. However, with the progression of cell differentiation in spermatogenesis it is possible notice differences between the numbers of spermatocytes in preleptotene/leptotene, pachytene and rounded spermatocytes between the two studies mentioned above, i.e.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, Sertoli cell and spermatogonia populations showed few variations between the animals evaluated. The average number of Sertoli cells observed was four per seminiferous tubule cross-section during stage 1 of CES and in the mean number of spermatogonia cells was two per cross-section, which were similar to the numbers observed as general averages by Andreussi et al [2] in the Nelore, Nelore mocho, Gir, Guzerá, and Tabapuã breeds, in addition to by Dias [35]. However, with the progression of cell differentiation in spermatogenesis it is possible notice differences between the numbers of spermatocytes in preleptotene/leptotene, pachytene and rounded spermatocytes between the two studies mentioned above, i.e.…”
Section: Discussionsupporting
confidence: 89%
“…However, with the progression of cell differentiation in spermatogenesis it is possible notice differences between the numbers of spermatocytes in preleptotene/leptotene, pachytene and rounded spermatocytes between the two studies mentioned above, i.e. the final yield in spermatogenesis is different between the breeds, with the Nelore breed producing the greatest final spermatogenesis yield [2]. On the other hand, Aguiar et al [36] Results published in rats [31] differ from those observed in bulls in the present study.…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…This genetic improvement can also be observed in the increased scrotal circumference of selected herds (Viu et al 2006;Martins et al 2011;Pinho et al 2013). The use of the scrotal circumference as the main parameter for the selection of bulls for breeding involves selecting the animals with higher sperm production and an increased testicular volume, which directly implies changes in the functional morphology of this organ and justifies the need for periodic updates of these measurements to characterize the evolution of the morphometric indexes of the testicular parenchyma (Unanian et al 2000;Andreussi et al 2013).The volumetric proportion of Leydig cells in the intertubular tissue and the quantitative parameters directly related to the seminiferous tubule, such as the tubule diameter, the thickness of the seminiferous epithelium and the tubule length (total length and length per gram of testicular parenchyma), are positively correlated with spermatogenic activity, providing information regarding the level of spermatogenic activity and constitute indicators of this activity in investigations involving testicular function (França and Russell 1998;Paula et al 1999). Despite the great importance of zebu cattle in tropical regions, there are few published studies on the process of spermatogenesis in these animals.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies such as Maia et al (2011), which trace a comparative study of the quality of semen in sheep, but without addressing the morphological aspects. In cattle, however, Andreussi et al (2014) developed this type of comparative study, and they found differences when evaluating the morphology of testis and spermatogenic yield between five Zebu cattle breeds used in Brazil (Nelore, Polled Nelore, Gir, Guzerá, and Tabapuã).…”
Section: Introductionmentioning
confidence: 99%